Star trek, the original series Volume 1 Episodes 2 & 3 - Shatner, William; Nimoy, Leonard; Doohan, James; Takei, George, 1937-; Roddenberry, Gene.; Paramount Home Video (Firm) (Hollywood, CA : Paramount Home Video, 1999)
Where no man has gone before (Episode 2, Stardate:1312.4) A tale of terror at the edge of the galaxy. Kirk must make a decision involving his best friend. The Corbomite maneuver (Episode 3, Stardate:1512.2)The Enterprise destroys a luminescent radioactive cube and is faced with a ship of pulsating lights commanded by Balok. Balok condemns the crew to death and Kirk must make a desperate escape plan that features the debut of Dr. McCoy.
Where no man has gone before -- Corbomite maneuver.
Videodisc release of the 1966 television show.
Based on "Star trek" created by Gene Roddenberry.
For specific features see interactive menu.
Directors, James Goldstone (Episode 2), Joseph Sargent (Episode 3).
William Shatner, Leonard Nimoy, James Doohan, George Takei.
DVD.
Keywords: Exploration of outer space; Outer space -- Drama; Drama; Science fiction television programs; Video recordings for the hearing impaired